The American National Standards of the Physical Education Teacher in the Curricula of the Jordanian Universities (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The purpose of this study was to identify the degree of existence of the American national standards of physical education teachers in the curricula of the Jordanian universities from the students' perspective in relation to the variables of the university, academic level, and gender. The sample consisted of (335) male and female students from four physical education faculties at the four major public Jordanian universities. The questionnaire of this study covered six dimensions and included (48) items, which reflect the American national standards for physical education teachers . The findings indicated that the American national standards of physical education teachers existed in the curricula of the Jordanian universities with a moderate degree. The results also showed that there were no statistically significant differences between male and female students in their view of the availability of American standards in college curricula. However, the results showed statistical differences due to the university and academic year variables, where the students of the University of Jordan recorded the highest averages, followed by the students of Yarmouk University, the Hashemite University and the University of Mutah, respectively., and s the fourth-year students recorded statistically higher averages than third-year students in colleges of physical education. The study recommends the need for curricula to keep pace with international standards, specifically the American ones under study.
Keywords: Curricula of Physical Education Colleges at the Jordanian Public Universities; the American National Standards of Physical Education Teachers; Third and Fourth-Year Male and Female Physical Education Students in Jordan